Haploinsufficiency of akt1 prolongs the lifespan of mice. - Aika Nojima (Public Library of Science (PLoS), 2013)
There is increasing evidence that nutrient-sensing machinery is critically involved in the regulation of aging. The insulin/insulin-like growth factor-1 signaling pathway is the best-characterized pathway with an influence on longevity in a variety of organisms, ranging from yeast to rodents. Reduced expression of the receptor for this pathway has been reported to prolong the lifespan; however, the underlying mechanisms are largely unknown. Here we show that haploinsufficiency of Akt1 leads to an increase of the lifespan in mice. Akt1 (+/-) mice had a lower body weight than their littermates with less fat mass and normal glucose metabolism. Ribosomal biogenesis and the mitochondrial DNA content were significantly reduced in these mice, along with a decrease of oxidative stress. Consistent with the results obtained in mice, inhibition of Akt-1 promoted longevity in nematodes (Caenorhabditis elegans), whereas activation of Akt-1 shortened the lifespan. Inhibition of Akt-1 led to a decrease of ribosomal gene expression and the mitochondrial DNA content in both human cells and nematodes. Moreover, deletion of ribosomal gene expression resulted in a decrease of the mitochondrial DNA content and normalized the lifespan shortened by Akt-1 activation in nematodes. These results suggest that an increase of mitochondrial amount and energy expenditure associated with enhanced protein synthesis accelerates both aging and the onset of age-associated diseases.